I Will Be a Better Teacher because of this CBL: Learning to Teach through Community-Based Learning - Gourd, Karen M. (International Journal of Research on Service-Learning in Teacher Education, 2014)
This study used interviews with eight teacher candidates to understand how they connect community-based learning projects to their process of learning to work with students different from the interviewees and teach for social justice. Findings indicate that community-based learning projects, integrated with other program components, supported candidates development as teachers of students with diverse backgrounds and as teachers oriented toward social justice. However, candidates did not learn the same thing at the same time. Community-based learning can provide opportunities for candidates knowledge and needs to be recognized and included in the process of learning to teach.